2014
DOI: 10.1021/jp507157e
|View full text |Cite
|
Sign up to set email alerts
|

All-Atom Molecular Dynamics Simulation of a Photosystem I/Detergent Complex

Abstract: All-atom molecular dynamics (MD) simulation was used to investigate the solution structure and dynamics of the photosynthetic pigment-protein complex photosystem I (PSI) from Thermosynechococcus elongatus embedded in a toroidal belt of n-dodecyl-β-d-maltoside (DDM) detergent. Evaluation of root-mean-square deviations (RMSDs) relative to the known crystal structure show that the protein complex surrounded by DDM molecules is stable during the 200 ns simulation time, and root-mean-square fluctuation (RMSF) analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 86 publications
3
22
1
Order By: Relevance
“…Various MD studies have shown that there is a heterogeneity in flexibility along the structure both at the level of the photosystems and of the single LHCs: as it could be expected, the most flexible domains are the ones more exposed to the membrane/water environment, i.e., external protein subunits in the case of PSII and PSI (Ogata et al 2013;Harris et al 2014;van Eerden et al 2017a, b, c) or exposed protein domains in the case of isolated LHCs Thallmair et al 2019). The most rigid parts are instead the core protein subunits of the photosystems and the core domains of the LHCs.…”
Section: (Sub)μs Timescale: Fast Conformational Changes Of the Photosmentioning
confidence: 92%
“…Various MD studies have shown that there is a heterogeneity in flexibility along the structure both at the level of the photosystems and of the single LHCs: as it could be expected, the most flexible domains are the ones more exposed to the membrane/water environment, i.e., external protein subunits in the case of PSII and PSI (Ogata et al 2013;Harris et al 2014;van Eerden et al 2017a, b, c) or exposed protein domains in the case of isolated LHCs Thallmair et al 2019). The most rigid parts are instead the core protein subunits of the photosystems and the core domains of the LHCs.…”
Section: (Sub)μs Timescale: Fast Conformational Changes Of the Photosmentioning
confidence: 92%
“…A remarkable example is the 200 ns MD simulation of the 3-million-atom system comprising the trimeric photosynthetic pigment-protein complex, photosystem I (PSI), embedded in a detergent belt of n-dodecyl- β -D-maltoside (DDM). The study performed by Frymier and coworkers [73]* 9 gave atomic resolution insight into the impact of the detergent on conformational dynamics of the system and its possible implications on PSI functionality.…”
Section: Large-scale MD Simulations Of Bioenergy Systemsmentioning
confidence: 99%
“… 9 [73]* MD simulations provide insight into the in vitro behavior of photosystem I (PSI) in detergent. …”
mentioning
confidence: 99%
“…12 Furthermore, for efficient energy conversion of PSI-integrated technologies, it is important to develop technologies that are reproducible and are able to control the orientation of PSI molecules on conductive substrates, while maintaining the functionality of the protein. 13 4 In such a process, the primary electron donor, the P 700 reaction center in PSI, is excited to P 700 * (E m = -1.3 V vs. SHE). The excited electron in P 700 * is passed to the primary electron acceptors, F A /F B (E m = -520 mV/-580 mV vs. SHE), which in turn reduces ferredoxin (E m = -440 mV vs. SHE).…”
Section: Introductionmentioning
confidence: 99%